ANALISIS PEMASARAN JERUK SIAM (STUDI KASUS: DESA LASEMBANGI KECAMATAN LASALIMU KABUPATEN BUTON) - Muzuna, Muzuna (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Buton, 2019)
This research has been conducted in Lasembangi Village, Lasalimu Subdistrict of Buton around June and July 2012. The aim of this study is to identify the types of marketing channels in Lasembangi Village, Lasalimu Subdistrict of Buton, to determine the marketing functions performed on each marketing channel, to determine the share profit producers in each marketing channel to determine the marketing efficiency of each marketing channel in Lasembangi Village, Lasalimu Subdistrict of Buton. The sampling method used by a tangerine farmer in the village of Lasembangi by Simple Random Sampling with 30 farmers randomly selected a sample of 120 farmers as a population. Sample totaling 3 traders and retailers 6. The data collected in this study consisted of primary data and secondary data. The data obtained from the field beforehand in a simple tabulated and analyzed in accordance with appropriate methods of analysis. Total samplings were 3 traders and 6 retailers. The data collected in this analysis consisted of primary and secondary data. Data obtained from the field in advance in a simple tabulated and evaluated in accordance with the correct methods of analysis. When the Ep price is ? 50 percent, Studies and analysis show that in this field of research there are three or more types of marketing channels: Channel 1: Farmer / Two Customer, Channel 2: Farmer / Towards Traders / Channel 3: Channel 1: Farmer / Towards the Market. On each marketing channel, marketing roles are performed the same. The share profit margin of manufacturers is different for every marketing channel. Networks I share 33.90%, Channels II 17.48% and Channels III 19.76%. In the village of Lasembangi, citrus marketing networks are already functioning.   Keywords: Orange, channel marketing, marketing margins, share profit margins, marketing efficiency